The minimum clinically important difference on the sleep disorders inventory for people with dementia. (11th September 2020) - Webster, Lucy; Martin, Alice; Livingston, Gill
Abstract : Objectives: Sleep disturbances in dementia causes distress to people with dementia and their family carers and are associated with care home admission. The Sleep Disorders Inventory (SDI) is a validated questionnaire of sleep disturbances in dementia often used to measure treatment effectiveness, but the minimum clinically important difference (MCID) is unknown. Methods: We triangulated three investigative methods to determine the MCID of the SDI. Using data on SDI from a randomised controlled trial (RCT) with 62 participants in an intervention for sleep disorders in dementia, we (1) calculated distribution‐based values where MCID = 0.33 of a SD (SD) (2) an anchor based approach using quality of life (measured using DEMQOL‐Proxy) as an anchor. We also employed a Delphi consensus process asking 12 clinicians, sleep researchers and family carers to rate which changes on vignettes were equivalent to a MCID. Results: We found that 0.33 SD in the SDI = 4.86. Reduction in SDI total score was not significantly correlated with improvement in DEMQOL‐Proxy (Pearson's correlation = −0.01; P = 0.96) score. The Delphi consensus required two rounds to reach a consensus and concluded that changes equivalent to three points on the SDI equated to the MCID. Conclusions: Taking into account both the distribution‐based values and the Delphi process we used a whole number at the midpoint and judged the minimum clinically important difference MCID to be equal to four points. We note the clinicians and carers opinions from the Delphi process determined the MCID to be lower at three points.